(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
Reverse osmosis (RO) desalination is an increasingly important technology for providing fresh water in water-scarce and semi-arid regions. However, one of its major environmental challenges is the generation of brine — a highly saline wastewater containing concentrated salts, chemicals and heavy metals. Improper disposal of brine can lead to soil salinization, groundwater contamination and marine ecosystem degradation. This article explores integrated and sustainable approaches to brine management, including concentration reduction technologies, zero-liquid discharge (ZLD) systems and resource recovery through salt and mineral extraction. It also examines the environmental impacts of brine discharge in semi-arid zones and proposes strategies for ecological protection, cost optimization and circular water economy integration. The study emphasizes the necessity of policy frameworks and innovative reuse models to ensure both environmental sustainability and economic feasibility in RO-based desalination systems.